Parenting di era digital untuk penguatan peran orang tua - Dewi, Adellia Fitria Marta; Nuraulia, Salsabila; Ridho, Achmad Hafidz Fatkhur (Maliki Interdisciplinary Journal, 2025)
This study discusses the impact of technological developments on human life, especially children who live in the digital era. In this context, it is important to understand how parental parenting plays a role in children’s social and emotional development. Parental involvement, behavior, and culture are very important in shaping children’s understanding of social interactions and empathy in children. Parental education influences how to effectively educate and care for children, as well as early childhood development, detailing the rapid physical and cognitive growth that occurs in the first year of life. Parents also model good behavior and provide a supportive environment for their children. . This period is very important because children experience rapid growth and lay the foundation for future development